1986
DOI: 10.1121/1.394082
|View full text |Cite
|
Sign up to set email alerts
|

An articulation index based procedure for predicting the speech recognition performance of hearing-impaired individuals

Abstract: An articulation index calculation procedure developed for use with individual normal-hearing listeners [C. Pavlovic and G. Studebaker, J. Acoust. Soc. Am. 75, 1606-1612 (1984)] was modified to account for the deterioration in suprathreshold speech processing produced by sensorineural hearing impairment. Data from four normal-hearing and four hearing-impaired subjects were used to relate the loss in hearing sensitivity to the deterioration in speech processing in quiet and in noise. The new procedure only requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(105 citation statements)
references
References 0 publications
3
100
0
2
Order By: Relevance
“…The present results demonstrate this dichotomy with opposite patterns of results between hearing aid and cochlear implant performance in speech and melody recognition: the hearing aid ͑containing the fine-structure cue at low frequencies͒ produced no speech recognition but significant melody recognition, while the cochlear implant ͑con-taining the temporal envelope cue͒ produced significant speech recognition but relatively poor melody recognition. The inability to recognize speech with only low-frequency information is consistent with classic articulation index studies, where low-pass filtered speech ͑Շ800 Hz͒ was relatively unintelligible ͑e.g., French and Steinberg, 1947;Pavlovic et al, 1986͒. However, this additional low-frequency acoustic information, when combined with the cochlear implant, produced significantly better speech recognition in noise than the implant alone condition.…”
Section: A Comparison Between Speech and Melody Recognitionmentioning
confidence: 99%
“…The present results demonstrate this dichotomy with opposite patterns of results between hearing aid and cochlear implant performance in speech and melody recognition: the hearing aid ͑containing the fine-structure cue at low frequencies͒ produced no speech recognition but significant melody recognition, while the cochlear implant ͑con-taining the temporal envelope cue͒ produced significant speech recognition but relatively poor melody recognition. The inability to recognize speech with only low-frequency information is consistent with classic articulation index studies, where low-pass filtered speech ͑Շ800 Hz͒ was relatively unintelligible ͑e.g., French and Steinberg, 1947;Pavlovic et al, 1986͒. However, this additional low-frequency acoustic information, when combined with the cochlear implant, produced significantly better speech recognition in noise than the implant alone condition.…”
Section: A Comparison Between Speech and Melody Recognitionmentioning
confidence: 99%
“…While some have reported accurate predictions using the AI (Aniansson, 1974;Lee and Humes, 1993), most studies have shown that speech intelligibility is worse than would be predicted by the AI (Fletcher, 1952;Dugal et al, 1978;Pavlovic, 1984;Pavlovic et al, 1986;Smoorenburg, 1992;Ching et al, 1998;Hogan and Turner, 1998), especially for listeners with moderate or severe losses. Thus, factors other than audibility must contribute to the difficulties experienced by the hearing impaired.…”
Section: Introductionmentioning
confidence: 99%
“…In order to be able to predict the speech intelligibility under such masking conditions, French and Steinberg ͑1947͒, Fletcher and Galt ͑1950͒, and later Kryter ͑1962a, b͒ initiated a calculation scheme, known as the Articulation Index ͑AI͒, which at present still is used by a number of investigators ͑Rankovic, 1998investigators ͑Rankovic, , 2002Hogan and Turner, 1998;Müsch and Buus, 2001;Turner and Henry, 2002;Dubno et al, 2002, 2003͒. In 1984, Pavlovic and others ͑Dirks et al, 1986Kamm et al, 1985;Pavlovic and Studebaker, 1984;Pavlovic et al, 1986;Studebaker et al, 1987 started to re-examine the AI calculation scheme, which has led to a new method accepted as the ANSI S3.5-1997 ͑1997͒. Since its revision in 1997, the method is named the Speech Intelligibility Index ͑SII͒.…”
Section: Introductionmentioning
confidence: 99%